Subjectivity. From the idea of interiority to the project of oneself in the social structure. Selected pedagogical implications - Andrzej Ryk (Studia z Teorii Wychowania)
The article concerns the issue of subjectivity understood here as a specific interiority. It shows, using selected examples, the development of this idea in philosophical thought, presenting its essential points of reference and breakthrough moments in its self-development. Next, using the example of structuration theory, it highlights its essential features related to self-reflexivity, self-reflexivity and the subjective autonomy of building an individual's own life project from a social perspective. The summary of the above analyzes is the isolation and presentation of selected threads important from the point of view of creating subjective pedagogy.